Android-based decision support system using MAGIQ-MARCOS for digital bank selection - Mahendra, Gede Surya; Wiradika, I Nyoman Indhi; Aryanto, Kadek Yota Ernanda (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
Choosing a digital bank is a challenge for anyone, especially due to cognitive biases that influence decision making. This study aims to develop an Android-based Decision Support System (DSS) using the MAGIQ MARCOS method to provide recommendations for digital banks that suit users’ preferences. The MAGIQ method is used to weight the main criteria, namely Application Performance (C1), Financial Reports (C2), and User Experience (C3), while MARCOS is used to rank digital banking alternatives. This study includes data collection through surveys and interviews, data processing using MAGIQ for weighting, and ranking alternatives using MARCOS. The results indicate that Jenius ranked first with a preference value of 0.7632 followed by Seabank with 0.7164 and Krom Digital Bank with 0.6983. These findings show that the system is able to differentiate alternatives based on user priorities. The system achieved an accuracy of 80.39 percent compared with students’ manual selections confirming that the recommendations align with actual user preferences. The recommendations generated by the system are consistent with the priorities of decision makers who value application quality and user experience. Use case testing also shows that all test scenarios function as expected. This research contributes to the development of technology based DSS to help students make more rational and data driven decisions in choosing a digital bank. Future work may integrate real time data updates and predictive analysis to improve recommendation accuracy and expand the MAGIQ-MARCOS method to other sectors that require multi criteria decision making.